Genre Features of Professional Screenplays in Russia in 1910s: Theory and Practice - A. G. Plotnikova (Научный диалог, 2024)
The article explores the genre dominants of Silver Age screenplays. Theoretical concepts of film dramaturgy are applied to the texts of A. A. Khanzhonkov’s “From the World of Mystery” (1915) and A. S. Voznesensky’s “God” (1918). The scientific novelty of the study lies in the comprehensive analysis of these screenplay texts for the first time. The relevance is justified by contemporary philology’s interest in the intermedial aspect of literature. The screenplays exhibit an orientation towards literary models: a wide range of linguistic devices (metaphors, similes, inversions), complex composition, psychological depth, and more. Cinematic expressiveness is realized through a system of modalities (real time, memories, dreams, imagination, altered consciousness, etc.), description of character movements, and “visual sound.” The study suggests that the genre of screenwriting in silent cinema fundamentally differs from subsequent eras and tends towards the epic rather than the dramatic genre. Discrepancies between directorial and literary scripts occurred early in the genre’s formation. A comprehensive examination of original realized screenplays could be key to understanding the reasons for the unsatisfactory results of writer-filmmaker interactions.